EVALUATION OF THICKNESS OF INTIMA-MEDIA COMPLEX OF COMMON CAROTID ARTERIES IN CHILDREN WITH JUVENILE ARTHRITIS AND SYSTEMIC LUPUS ERYTHEMATOSUS - A.B. Sugak; I.V. Dvoryakovskiy ("Paediatrician" Publishers LLC, 2010)
Rheumatic diseases in adults are associated with accelerated atherosclerosis, and its early signs can be stated by the thickening of intima-media complex of common carotid arteries (CCA). This symptom is detected during ultrasound examination in 49% of children with systemic lupus erythematosus, in 24% of patients with juvenile rheumatoid arthritis and in 13% of children with juvenile spondylarthritis. Besides, 36% of children with systemic lupus erythematosus and 17% - with systemic type of juvenile rheumatoid arthritis had structure changes of CCA wall. A dependence of these disorders on cholesterol and glucose levels in blood serum, overweight and Cushing syndrome, age, duration and activity of a disease, levels of ESR, C-reactive protein and white blood cells was not showed. Authors detected a correlation between the thickness of intima-media complex of CCA and hemostasis parameters.Key words: children, juvenile arthritis, systemic lupus erythematosus, intima-media complex, ultrasound diagnostics.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(2):64-69)